Notes from the Field: Results from the Parent Acceptance of Pediatric Integrated Care Survey. (February 2021) - Bruni, Teryn; Birnbaum, Richard; Turnier, Luke; Caserta, Abigail; Maragakis, Alexandros; Tennant, Katherine; Lancaster, Blake
Objective: To collect data and gain an understanding of parental satisfaction with and attitudes toward treatment in a pediatric integrated primary care (IPC) model. Data Sources: Primary data were collected across the United States over the course of a few months. Study Design: The 35-item, Parent Acceptance of Pediatric Integrated Care Survey (PAPICS) was developed by a panel of IPC experts. The survey was then distributed through the Qualtrics Panels Service with recruited participants (i.e., parents with children under 18-years-old) receiving a 4.00 incentive for their involvement. Data Collection/Extraction Methods: A single exploratory factor analysis was performed along with four factor retention tests and clinical judgment to guide factor selection. A 5-factor structure was selected. Principal Findings: Parents reported a high level of comfort with an IPC model and a favorable attitude toward child therapy, with some concerns regarding psychological stigma and privacy. Notable variation in parents' beliefs regarding one-on-one psychological service delivery were observed. Conclusions: Results provided evidence for parental openness to an IPC model. Findings also highlighted potential fundamental misunderstandings regarding evidence-based psychological treatment methods for children and adolescents.